John Collier’s Paintings of Clytemnestra (Studies in Ancient Art and Civilisation, 2024)
The British artist John Maler Collier produced two paintings of the legendary Mycenaean queen Clytemnestra, in which he incorporated elements of contemporary archaeological discoveries. Archaeological excavations in Europe in the late 19th century included Heinrich Schliemann’s work at Hisarlık (identified as Troy) and Mycenae. These were followed in the early 20th century by archaeological excavations on Crete, revealing Minoan society, including those by Arthur Evans. Collier gave the paintings, one from 1882 and the other from around 1914, the simple title ‘Clytemnestra’, both depicting the moment the queen has just murdered her husband Agamemnon at Mycenae, as related by several classical authors. The earlier version of the painting depicts Clytemnestra wearing a costume reminiscent of Archaic or Classical Greece, albeit with accessories that have parallels from much earlier periods, specifically Early Bronze Age Hisarlık, Mycenaean Greece and Early Iron Age Greece. The later version shows Clytemnestra wearing a costume that has elements from Minoan Crete, radically different from the earlier version, although again with Trojan and Mycenaean accessories. In both paintings, Collier created an architectural setting featuring Mycenaean motifs, very accurately rendered but used in a somewhat anachronistic manner. The author considers the two differing depictions of Clytemnestra using the methodology of identifying specific archaeological objects that Collier incorporated into his two paintings and, in addition, suggests ways in which he could have encountered them. The conclusion is that for both paintings, Collier followed the principles outlined in his treatise ‘A Manual of Oil Painting’ to make use of all knowledge available to him at the time of the latest archaeological discoveries from the Aegean Bronze Age.